COVID-19 anxiety and hygiene status in vocational schools of health services students in Turkey: A multicenter study - Pirincci, Edibe; Arca, Muhammed; Sen, Mehmet Ali; Atici, Erhan; Varsak, Suleyman; Yarasir, Ezgi; Deveci, Suleyman Erhan (Sage Publications Inc, 2021)
BACKGROUND: While the coronavirus (COVID-19) pandemic creates fear and anxiety on the students' academic achievement, the risk of an infectious disease may negatively affect education by reducing the concentration ability of students. Thus, it is essential to evaluate the knowledge, behaviors, anxiety levels, and hygiene status of students. OBJECTIVE: This study aimed to investigate the knowledge, behavior change, anxiety, and hygiene status of university students about COVID-19. METHODS: The investigation was conducted with students of three vocational schools of health services located in different provinces of Turkey (n = 1055). Data collected by an online survey consisted of knowledge questions about COVID-19, items about behavior change, the hygiene behavior scale (HBS), and the Generalized Anxiety Disorder 7 (GAD-7) scale. RESULTS: The knowledge scores ofwomen were significantly higher than the scores of men. Of the students, 59.6% showed positive hygiene behaviors, and 31.5% had anxiety. Female students' total HDC scale score was significantly lower than that of men, and the total HDC scale score of those who received hand hygiene education was significantly lower than that of participants who did not receive training, which shows a positive hygiene behavior. The total GAD-7 scale score of women was significantly higher than that of men. More than half of the students showed positive hygiene behaviors, and about a third had anxiety. CONCLUSIONS: Based on the study's results, psychological support and training should be provided to students.
Keywords: Behaviors; coronavirus; knowledge; psychological factors; university students